2009
DOI: 10.1158/1541-7786.mcr-08-0532
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Activating Mutations Are Associated with Local Copy Gain

Abstract: Although activating mutations and gains in copy number are key mechanisms for oncogene activation, the relationship between the two is not well understood. In this study, we focused on KRAS copy gains and mutations in non-small cell lung cancer. We found that KRAS copy gains occur more frequently in tumors with KRAS activating mutations and are associated with large increases in KRAS expression. These copy gains tend to be more focal in tumors with activating mutations than in those with wild-type KRAS.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
67
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 33 publications
10
67
0
Order By: Relevance
“…One patient with an EPAS1 mutation also had copy number gain of the EPAS1 locus. The combination of activating mutations and copy number gain has previously been reported for EPAS1 (Comino-Mendez et al 2013), as well as for other oncogenes (Modrek et al 2009). …”
Section: Discussionmentioning
confidence: 59%
“…One patient with an EPAS1 mutation also had copy number gain of the EPAS1 locus. The combination of activating mutations and copy number gain has previously been reported for EPAS1 (Comino-Mendez et al 2013), as well as for other oncogenes (Modrek et al 2009). …”
Section: Discussionmentioning
confidence: 59%
“…7,10 Recently, it was shown that reactivation of p53 in a KRAS G12D mouse model of non-small-cell lung carcinoma lead to tumor regression only in tumors with KRAS signal elevated through the amplification of the mutant allele and loss of wild-type allele. 17,18 In this larger series of KRAS-mutated lung adenocarcinomas, we confirm and expand the finding that KRAS MASI correlates with worse clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in a subgroup analysis, the presence of KRAS MASI maintained its adverse prog- The quantitative nature of the direct sequencing and its reliability in assessing allelic imbalance was previously shown both on cell lines and in clinical tumor samples. 7,10,19 In addition to sequencing electropherogram and FISH, previous studies of KRAS allelic imbalance in lung adenocarcinomas used such methods as qPCR and SNP ( Table 2). The number of clinical samples was lower, and the ethnicity of studied patients was distinct from the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of events driving distinct tumor phenotypes requires interrogation of multiple omics dimensions on appropriate, well-annotated tumor specimens, and the interpretation of these molecular data in a biologically and clinically meaningful way (Hood et al 2004;Gondek et al 2007;Yamamoto et al 2007;Cancer Genome Atlas Research Network 2008;Dunbar et al 2008;Gandhi et al 2009;Modrek et al 2009;Segditsas et al 2009;Soh et al 2009;Wang et al 2010;Vidal et al 2011). Using a multi-omics systems-based approach to the analysis of patient cancer samples will enhance our understanding of cancer biology and accelerate the translation of omics research.…”
Section: A Multidimensional Approach To Cancer Omicsmentioning
confidence: 99%